Isolated Cerebral Metachronous Metastasis in Fibular Osteosarcoma: A Rare Case Report with Review of Literature - Nayak, Manoj Kumar; Rastogi, Sameer; Sebastian, Leve Joseph; Tansir, Ghazal; Narwal, Anubhav (Indian Journal of Medical and Paediatric Oncology, 2023)
Isolated brain involvement is rarely reported as isolated metachronous metastasis from osteosarcoma. Herein, we report a case of fibular osteosarcoma in a young female who presented with solitary hemorrhagic metachronous cerebral metastasis after years of disease-free interval. Imaging showed a large mass lesion in the right posterior temporal lobe with internal areas of bleed not associated with calcification or ossification mimicking high-grade glioma. No other sites of distant metastases were found on the workup. Two-dimensional echocardiography was done to rule out any cardiac anomaly, including the shunt defect, but no abnormality was detected. She was operated for the cerebral lesion, and histopathology of the resected specimen showed osteosarcoma. The patient was started on chemotherapy and is doing well so far. This case presents a unique scenario of osteosarcoma with an isolated lesion in the brain without any other site of distant metastasis.
Keywords: osteosarcoma; brain metastasis; high-grade glioma; lung metastasis